Surface free energy of 10 tropical woods species and their acrylic paint wettability. Issue 2 (17th January 2020) - Martha, Resa; Dirna, Fitria C.; Hasanusi, Aulia; Rahayu, Istie S.; Darmawan, Wayan
Abstract: The surface free energy (SFE) of woods and their wettability are important characteristic for wood painting. No information is available regarding the SFE and wettability of Indonesian tropical woods. The purpose of the study was to determine the SFE and wettability of 10 Indonesian tropical woods. The woods tested in this study were fast-growing species from plantation of teak, sengon, jabon, pine, and species from natural forest of ramin, meranti, mahagony, camphor, keruing, and ebony. Surface roughness was measured by a profilometer, while wettability was determined by sessile drop method. The SFE values were calculated based on the Rabel method. Wettability was characterized by constant contact angle change rate ( K ) using the Shi and Gardner (S/G) model. The results showed that the mean roughness (Ra) value of fast-growing species from plantation was 13.58 μm and of species from natural forest was 10.73 μm. The SFE of woods varied from 36.00 mJ/m 2 in the Meranti to 69.68 mJ/m 2 in the Sengon. It was observed that the Meranti wood with the lowest value of SFE provided the lowest value of K (0.01) which indicated the poorest in wettability. The Sengon wood with the highest value of K (0.06) should provide the best wettability for the acrylic paint.